2006
DOI: 10.1242/dev.02529
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of gene expression in the digit forming area of the mouse limb bud by SHH and gremlin 1/FGF-mediated epithelial-mesenchymal signalling

Abstract: Spatially and temporally coordinated changes in gene expression are crucial to orderly progression of embryogenesis. We combine mouse genetics with experimental manipulation of signalling to analyze the kinetics by which the SHH morphogen and the BMP antagonist gremlin 1 (GREM1) control gene expression in the digit-forming mesenchyme of mouse limb buds. Although most mesenchymal cells respond rapidly to SHH signalling, the transcriptional upregulation of specific SHH target signals in the mesenchyme occurs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 44 publications
7
117
0
Order By: Relevance
“…−/− embryos (Aoto et al, 2002;Litingtung et al, 2002;Panman et al, 2006;te Welscher et al, 2002;Zúñiga et al, 1999). Collectively, these studies illustrate the profound importance of Shh in counteracting Gli3-mediated repression of target genes.…”
Section: ;Gli3mentioning
confidence: 99%
See 2 more Smart Citations
“…−/− embryos (Aoto et al, 2002;Litingtung et al, 2002;Panman et al, 2006;te Welscher et al, 2002;Zúñiga et al, 1999). Collectively, these studies illustrate the profound importance of Shh in counteracting Gli3-mediated repression of target genes.…”
Section: ;Gli3mentioning
confidence: 99%
“…To determine the time period during which GRE1 requires Gli activator for enhancer activity in the posterior limb, we used an established ex vivo limb bud culture assay, treating GRE1LacZ +/− limb buds with the Hh pathway inhibitor cyclopamine (Panman et al, 2006). We cultured one forelimb in media containing cyclopamine while the contralateral side was cultured in control media, providing an internal control for staging and embryo variability (Fig.…”
Section: Enhancer Activity Requires Sustained Gli Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the genes involved in the Shh/Grem1/Fgf feedback loop is dynamic and dependent on the timing and levels of other components in the regulatory network (16)(17)(18)(19). To investigate the effect of removal of Hh signaling from the AER on the components of the Shh/Grem1/Fgf feedback loop, double RNA in situ hybridizations for Shh and Fgf4 or Fgf8 were performed on normal and Msx2-Cre;Smo flox/flox embryos.…”
Section: Hedgehog Signaling In the Aer Is Required For Formation Of Amentioning
confidence: 99%
“…We have investigated the transcriptome alterations between Shh-deficient and wild-type forelimb buds around E10.5 (35-36 somites), which corresponds to the period during which limb bud development largely depends on SHH signalling Zhu et al, 2008;Panman et al, 2006). Unexpectedly, this analysis revealed that forelimb buds of Shh-deficient mouse embryos were molecularly proximalised as the expression of several proximal genes was upregulated and their domains extended distally.…”
Section: Introductionmentioning
confidence: 99%